Racial/Ethnic Disparities in Influenza and Pneumococcal Vaccinations Among Nursing Home Residents: A Systematic Review - Travers, Jasmine L (Gerontologist, 2018)
This systematic review analyzes research examining racial/ethnic disparities in influenza and pneumococcal vaccination coverage between White and racial/ethnic minority (Black and Hispanic) nursing home residents. A review of the literature for years 1966–2014 using Medline, Web of Science, and PubMed was conducted. The Epidemiological Appraisal Instrument was used to appraise the quality of the 13 included studies. Overall, articles were strong in reporting and data analysis, but weak in sample selection and measurement quality. Disparities between vaccination coverage among racial/ethnic minorities versus Whites ranged from 2% to 20% for influenza and 6% to 15% for pneumococcal vaccination. Researchers reported racial/ethnic minorities were more likely to refuse vaccinations and less likely to have vaccinations offered and their vaccination status tracked compared to Whites. Policies/strategies that focus on ensuring racial/ethnic minorities are offered influenza and pneumococcal vaccinations and their vaccination status are tracked in nursing homes are warranted. Updated evaluation on vaccination disparities is also needed.